Peran Bidan di Desa dan Cakupan Pemberian Kapsul Vitamin A pada Ibu Nifas - Vonny Khresna Dewi, Mohammad Hakimi, Agung Suhadi (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Vitamin A deficiency remains a major nutritional problem in Indonesia. Based on the survey on Vitamin A in 1992, the prevalence of Vitamin A deficiency, among others, of xerophthalmia is about 0.33. A high dose of Vitamin A supplementation for post partum mothers is considered as one solution of reducing Vitamin A deficiency. National guide recommends that 100% of post partum mothers receive one capsule of high dose of Vitamin A; however, data from Nutrition and Health surveillance System (NSS) shows that some rovinces in Indonesia still have low coverage of Vitamin A supplementation, that is, only about 15-25%. In fact, until November 2006 the coverage of Vitamin A supplementation in Tapin District, South Kalimantan, was 33.69.Objectives: To investigate the relationship between village midwifes’ role and the coverage of Vitamin A supplementation for post partum mothers.Methods: This was an observational study with cross sectional study design. Subjects were 62 village midwifes’ in Tapin District, South Kalimantan Province.Results: There was a significant relationship between village midwifes’ role and the achievement of Vitamin A supplementation for post partum mothers. This means that the good role of village midwifes would increase the achievement of Vitamin A supplementation coverage almost five times higher than the bad one. This was proven by chi-square statistical test with RP 4.55, CI 95% 1.42-14.56 and p=0,003.Conclusions: There is a significant relationship between village midwifes’ role and the achievement of Vitamin A supplementation coverage for post partum mothers, so that midwifes’ role should better be scaled up to improve maternal and child health.Keywords: Role, village midwifes, Vitamin A coverage, post partum mothers.